Mulighedens uendelighed – uendelighedens mulighed: Bidrag til en postmoderne håbsforståelse med udgangspunkt i Kierkegaards subjektivitetsteori og etik - Mortensen, Anna Ravn (Dansk teologisk tidsskrift, 2024)
The article investigates the possibilities and limitations of a religious Christian hope from a postmodern perspective. It argues that Søren Kierkegaard’s Christian understanding of hope as ambiguous, despiteful, and ethical is in alignment with Gianni Vattimo’s postmodern theory of kenosis as the essence of secularity. The argument proceeds in three steps. The first section outlines the challenge and the potential of the postmodern. The second section analyzes Kierkegaard’s understanding of hope. The third section sketches how Vattimo’s postmodern theory contrasts the pragmatic, scientific, and nihilistic hopes of today and aligns with Kierkegaard’s understanding of hope.